DECAPITATION OF MAN HEADS IN ACARI VALLEY, PERU - Valdez, Lidio M. (2010)
Archaeological excavations at Amato, a site established at the beginning of the Early Intermediate period (circa 50 BC – 300 AD) in the Acari Valley of the Peruvian south coast, uncovered two isolated human heads from different contexts. One head was found near an area where dozens intentionally decapitated skeletons were recovered. The second head was located in association with the main wall that encloses the site. Both heads were buried in similar fashion to Early Intermediate period south coast trophy heads; however, these heads from Amato were not culturally modified (e.g. perforated frontal bone and/or artificially enlarged foramen magnum). These two isolated heads demonstrate that not all human decapitation in the Acari Valley was for the purposes of securing trophy heads. Based on these findings, we suggest that the purpose and motivation for human decapitation and head-taking in the past was complex.